Genetic predictor of current suicidal ideation in US service members deployed to Iraq and Afghanistan. (June 2019) - ,; Wynn, Gary; Russell, Dale W.; Ursano, Robert J.; Zhang, Lei; Hu, Xian-Zhang; Benedek, David M.; Fullerton, Carol S.; Forsten, Robert D.; Naifeh, James A.; Li, Xiaoxia
Abstract: Objective: Suicide is one of the ten leading causes of death in United States and the suicide rate in the military population has increased since the start of the Iraq and Afghanistan wars. However, few biomarkers for current suicidal ideation (CSI) have been identified. The current study examined the association of four candidate genes with CSI in active duty US Army Special Operations Command and National Guard units (n = 3, 889) who served in Iraq and Afghanistan between November 2009 and July 2014. Methods: Current PTSD symptoms and CSI were assessed using the PTSD Checklist (PCL) and PHQ-9, respectively. Traumatic events were assessed using items from the Life Events Checklist (LEC) that met the DSM-IV PTSD criteria of a traumatic stressor. All genotypes of saliva DNA were discriminated using the TaqMan 5′-exonuclease assay. Results: The associations between CSI and brain-derived neurotrophic factor (BDNF), FK506 binding protein (FKBP5), catechol-O-methyltransferase (COMT), or S100A10 (p11) were examined. We found CSI was associated with BDNF (OR = 1.5, 95% CI = 1.5–1.8, P = 0.0002), but not FKBP5, COMT and p11. Female soldiers reported CSI more often than males (χ2 = 7.403, p = 0.0065), although gender did not affect CSI severity. In addition, associations were found between CSI and depression, PTSD, and BDNF, but not traumatic events. The BDNF Val66Met contributed to the severity of CSI even after adjusting to PTSD, depression and LEC. Conclusions: The associations of BDNF with CSI and its severity suggest that BDNF may be a predictor of suicidal risk and present an opportunity to develop laboratory tools with clinical implications in suicide prevention and treatment. Highlights: CSI and its severity are associated with BDNF in service members. The interaction of depression or PTSD with BDNF is associated with CSI. BDNF may be a predictor of suicidal risk.